SUATU PENELITIAN TENTANG KEMAMPUAN MAHASISWA TAHUN KETIGA PROGRAM STUDI PENDIDIKAN BAHASA INGGRIS FKIP UR DALAM MEMAHAMI ARTIKEL BERITA BERBAHASA INGGRIS - Ardi Wiranata; Fadly Azhar; Masyhur ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The purpose of this study is to find out the third year students’ ability of English Study Program in comprehending English news articles. This research focuses on finding factual information, finding main ideas, locating the meaning of vocabulary in context, identifying references, and making inferences based on English news articles. Data were collected using reading comprehension test with multiple choice type. The test contained 30 items. The try out was conducted to check the validity and reliability of the test. The research findings are as follows. First, the ability of the students in comprehending English news articles is 67 which is in Average to Good level. Second, the students’ mean score in finding factual information is 71, the mean score in finding main ideas is 59, the mean score in identifying references is 73, the mean score in making inferences is 61, and the mean score in locating the meaning of vocabulary in context is 67. Third, the highest score obtained by the students is in identifying references that falls into Average to Good ability level, and the lowest score that the students get is in finding main ideas that falls into Poor to Average ability level.Keywords: Ability, Comprehending, News Articles.